Pertanggungjawaban Hukum Pelaku Usaha E-Commerce Atas Terjadinya Pencurian Data Konsumen Melalui Aplikasi Tokopedia Berdasarkan Pasal 19 dan Pasal 62 Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Nugraha, Sakti; Andayani, Dwi; Tumanggor, M.S (Universitas Ekasakti, 2023)
In Indonesia, in practice, it is known that carrying out business and trade through electronic media or e-commerce, such as through online shopping applications, such as Shopee, TokoPedia, BukaLapak, and OLX, has the risk of violating the law and rights, both violations of the law and the rights of sellers and buyers. , as well as to business actors, the fact is that the Tokopedia application was lost due to theft of consumer data carried out by irresponsible parties, which happened in the case of Decision 235/PDT.G/ 2020/PN.JKT.PST, which in this case It is known that there has been theft of consumer data using the Tokopedia application. The aim of this research is to provide legal protection for consumers regarding personal data in e-commerce applications, and to formulate the legal responsibility of e-commerce business actors for theft of consumers' personal data. The research method used in this research is a normative juridical research method. The materials studied are primary, secondary and tertiary legal materials. Then the results obtained in this research are based on the analysis carried out by researchers. The responsibility of e-commerce business actors regarding the security of consumers’ personal data is often ignored by the government, and it is not uncommon for e-commerce business actors to escape legal responsibility, even though it is clearly known that data Consumers’ personal privacy being stolen can of course result in many things, such as misuse of data for general fraud purposes, debt and receivable fraud, and other problems which of course can be detrimental to consumers, in this case the public in general. The issue of legal protection of personal data has not yet received special attention from either the government or law enforcement officials.